Early recurrence of adult type ovarian granulosa cell tumor in sigmoid colon: a case report - Marjaneh Farazestanian; Elham Sharafkhani; Mohadeseh Nazari Fathabad (Mashhad University of Medical Sciences, 2024)
Introduction: Ovarian granulosa cell tumors (GCT) include 2-3% of ovarian cancers. This study reported a rare case of granulosa at the age of 35 with early recurrence in sigmoid colon. Case presentation: A 35-year-old female, Noli Gravid, with a history of primary infertility and a complaint of abdominal pain referred to Ghaem Hospital in Mashhad, Iran. With the diagnosis of ovarian mass, she underwent laparotomy. The intraoperative frozen examination was for an ovarian granulosa tumor. Right salpingo-opheretomy with surgical staging and endometrial curettage were done. The final pathology was adult-type granulosa tumor and other samples were normal. Three cycles of chemotherapy were performed. After 18 months of non-follow up, she returned with a complaint of abdominal pain. An 8 cm mass on the left side of the pelvis was reported. She was candidate for surgery. There was a mass attached to the mesenter of the sigmoid colon which was resected and sent for frozen. Frozen analysis reported the recurrence of the granulosa tumor. A total hysterectomy with a left salpingo-oophorectomy was performed. Then she underwent pelvic radiotherapy. Conclusion: Recurrence is the main cause of patients' death. Due to late recurrence, patients should be trained to pay attention to the symptoms of recurrence in order to cooperate in long-term follow-up for early diagnosis of recurrence band treatment. Considering the rare cases of extra-pelvic and extra-genital recurrences, there is a need for new treatment strategies to be carried out in the form of clinical trials to improve the quality of life of patients and prevent frequent recurrences leading to their mortality.